The Use of Census-Based Geographic Automata Systems in Understanding the Spread of Infectious Disease. - Vitale, Joseph (2010)
Keywords: dept.csc; faculty_collection; sabbatical_report

Zigbee Wireless Sensor and Control Network - Elahi, Ata; Gschwender, Adam (Prentice Hall, 2010)
Topics include: Fundamental wireless concepts: OSI Model, error detection, the ISM Band, modulation, WLAN, FHSS, DSSS, Wireless MANs, Bluetooth ; ZigBee essentials: applications, characteristics, device types, topologies, protocol architecture, and expanded ZigBee PRO features ; Physical layer: includes frequency bands, data rate, channels, data/management services, transmitter power, and receiver sensitivity ; MAC layer: data/management services, MAC layer information base, access methods, and frames ; Network layer: data entities, NIB, device configuration, starting network, addressing, discovery, channel scanning ; Application support sublayer and application layer: includes profiles, cluster format, attributes, device discovery, and binding ; ZigBee network security: includes encryption, trust center, security modes, and security management primitives ; Address assignment and routing techniques ; Alternative technologies: 6lowpan, WirelessHART, and Z-wave.:--pub. desc.
Keywords: Industrial applications; Industrial applications; Radio frequency; Personal communication service systems; Standards; Sensor networks; Low voltage systems; dept.csc; faculty_collection

An information system for multi-instrument atmospheric laser radar studies - Sharma, N.; Parikh, J.A. (2010)
In this paper we describe an information system that we have designed for students and researchers to conduct atmospheric studies using data that they have collected from multiple atmospheric instruments including two laser radar (lidar) systems. The lidar systems available for research include a monostatic Micro Pulse Lidar System and a bistatic imaging CLidar system. Complementary instruments for data analysis and ground truth specification include a nephelometer, sunphotometers and a weather station. Information structures within the system allow users to 1) label, describe and archive raw and derived datasets from multiple atmospheric instruments with associated metadata using NetCDF format, 2) link together coincident and co-located datasets from different instruments and 3) identify owner and verify user access rights of raw and derived datasets. Data analysis software tools have been developed in MATLAB to characterize and remove instrument artifacts based on experimental lidar studies, to analyze clear sky data to determine variability in atmospheric aerosol content over time and altitude, and to investigate cloud and aerosol patterns.
Keywords: Aerosol patterns; Atmospheric aerosols; Atmospheric instruments; Atmospheric laser; Atmospheric studies; Bistatic; Clear sky; Co-located; Cybernetics; Data analysis softwares; Data sets; Ground truth; Information science; Information structures; Information systems; Instruments; Laser radar; Lasers; Lidar; Lidar systems; Metadata; Micro pulse lidar; Monostatic; Optical radar; Sun-photometers; User access; Weather stations; dept.csc

A performance model of gossip-based update propagation - Antonios, Imad; Dhar, Reetu; Zhang, Feng; Lipsky, Lester (2010)
We consider the problem of propagating an update to nodes in a distributed system using two gossiping protocols. The first is an idealized algorithm with static and dynamic knowledge of the system, and the second is a simple randomized algorithm. We construct a theoretical model that allows us to derive work and completion time statistics under varying transmission delay distributions. Numerical results are obtained for both exponential and nonexponential transmission times using linear-algebraic queueing theory techniques. Additionally, we present the results of simulation experiments showing that under node churn assumptions, the randomized algorithm's performance is qualitatively different than in a fault-free system. © 2010 IEEE.
Keywords: Algorithms; Completion time; Distributed systems; Gossiping protocols; Linear-algebraic; Numerical results; Performance Model; Queueing theory; Randomized Algorithms; Simulation experiments; Static and dynamic; Theoretical models; Transmission delays; dept.csc